Long‐term clinical outcome and mortality risks after paclitaxel‐coated balloon angioplasty in patients with peripheral artery disease: An observational clinical study. Issue 1 (26th January 2021) - Schahab, Nadjib; Prengel, Ann‐Kathrin; Mahn, Thorsten; Schaefer, Christian; Fimmers, Rolf; Nickenig, Georg; Zimmer, Sebastian
Abstract: Background and aims: Drug‐eluting devices (DEDs) are usually used as a standard therapy for revascularization in femoropopliteal artery disease. Randomized controlled trails have found that DEDs with paclitaxel result in superior patency rates and decreased target lesion revascularization. A meta‐analysis by Katsanos et al indicated an increased long‐term mortality in patients treated with paclitaxel‐coated devices. The aim of this observational clinical study was to assess the long‐term clinical outcomes and mortality risk after paclitaxel‐coated balloon angioplasty in patients with symptomatic peripheral artery disease. Methods: We retrospectively evaluated 287 patients with peripheral interventions, including 173 drug‐coated balloon (DCB) angioplasties and 114 plain old balloon angioplasties (POBA), performed at our center between 2015 and 2018. Results: There were no significant differences in mortality rates between patients who received DCB angioplasty and those who received POBA. In the first year, the hazard ratio (HR) for DCB angioplasty was 0.59 (95% confidence interval [CI] 0.31 to 1.12, P = .104). After 2 years, this HR was 0.64 (95% CI 0.36‐1.17, P = .145), while the 3‐year and 4‐year HR increased to 0.71 and 1.30 (3‐year: 95% CI 0.37‐1.33, P =, 283; 4‐year: 95% CI 0.55‐3.08, P = .546). No paclitaxel dose‐response relationship with mortality rate was identified when adjusted for key predictors of mortality. Conclusions: Analyses of patient level data identified no significant mortality differences between DCB angioplasty and POBA after 4 years of follow‐up. Furthermore, there was no dose‐response relationship between paclitaxel and mortality. These findings demonstrate that paclitaxel DCB is safe. Further long‐term multicenter studies are needed to determine the risk of late mortality. Abstract : This study aimed to assess the long‐term clinical outcomes and mortality risk after paclitaxel‐coated balloon angioplasty in patients with symptomatic peripheral artery disease.Analyses of patient level data identified no significant mortality differences between DCB angioplasty and POBA after four years of follow up. Furthermore, there was no dose‐response relationship between paclitaxel and mortality. These findings demonstrate that paclitaxel DCB is safe. Further long‐term multicenter studies are needed to determine the risk of late mortality.